Introduction: Hellenic Tradition in 19th-21st Centuries in the Spanish and Argentinian Dramas - Alvarado Teodorika, Tatiana; Grigoriadou, Theodora (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Introduction to the dossier
Keywords: theatre; classical tradition; spanish teathre; argentina theatre